The Indian Indie Game Development Scene - History and Cultural Heritage as Game Themes - Zeiler, Xenia (Gamevironments, 2016)
While the Indian indie game development scene is still relatively young, it has already lived through big changes. Like in many regions worldwide, indie game developers in India have to negotiate between practical issues, for example regarding market requirements and expectations, and committed ambitions, for example regarding creative aspirations in art design and game content. On the one hand and in order to persist in the ever extending industry, they need to acknowledge mainstream wants and practical demands from especially (though not exclusively) the Indian game market which at present is characterized by an overall dominance of mobile card and casino games. On the other hand, we see that especially Indian indie developers increasingly reflect on the role of Indian cultural heritage (including elements from history, architecture, music, etc.) for India produced games. This turn to own roots, to implement Indian cultural and historical heritage in games, is now visible in a number of games which have been recently Greenlit on Steam and are in the final production phases, such as Asura (2017 forthc.), Antariksha Sanchar (2017 forthc.), and others.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé